2014
DOI: 10.15832/tbd.02227
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Purchase Intention toward Safety Labeled Dairy Products in the Black Sea Region of Turkey

Abstract: About half of raw milk production in Turkey is sold under unsanitary conditions in open-air markets or by street vendors without following appropriate food safety standards and the consumers face a very high risk of consuming potentially unsafe dairy products. This research aims to assess consumers' awareness and attitudes about food safety, and to assess the market potential of certified labeled dairy products by determining consumers' purchase intention toward such products. The data was collected from a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Fogyasztói preferenciák és motivációk Baker et al, 2009;Carson et al, 2016;Conner et al, 2010;Dodds et al, 2014;Dukeshire et al, 2015;Fehrenbach -Wharton, 2012;Garner -Ayala, 2018;Grebitus et al, 2017;Gumirakiza et al, 2014Gumirakiza et al, , 2017Halldorsdottir -Nicholas, 2016;Kadanali -Demir, 2018;Shi -Hodges, 2016;Spilkova et al, 2013] Jellemző fogyasztók a termelői piacokon Abelló et al, 2014;Berg -Preston, 2017;Grebitus et al, 2017 Fogyasztók és termelők közötti kölcsönhatásokat, motivációs különbségek Carson et al, 2016;Hunt, 2007;Leiper -Clarke-Sather, 2017 Termelői piacok működésében bekövetkező változások Bett et al, 2013;Blasi et al, 2015;Halldorsdottir -Nicholas, 2016 Helyi élelmiszerekkel szemben felmerülő attitűdök megítélése Asebo et al, 2007;Brown, 2003;Conner et al, 2010 Termelői piacok és a kereskedelmi egységek termékei közötti különbségek Bavorova et al, 2016 Fogyasztói tudatosság, fenntarthatóság és a termelői piacok környezetvédelmi előnyeinek fogyasztói észlelése Bozoglu et al, 2014;Szabó -Juhász, 2015;Dukeshire et al, 2015;Grebitus et al, 2017;Jadudova et al, 2018;Polimeni et al, 2018 Forrás: saját szerkesztés…”
Section: Példákunclassified
See 1 more Smart Citation
“…Fogyasztói preferenciák és motivációk Baker et al, 2009;Carson et al, 2016;Conner et al, 2010;Dodds et al, 2014;Dukeshire et al, 2015;Fehrenbach -Wharton, 2012;Garner -Ayala, 2018;Grebitus et al, 2017;Gumirakiza et al, 2014Gumirakiza et al, , 2017Halldorsdottir -Nicholas, 2016;Kadanali -Demir, 2018;Shi -Hodges, 2016;Spilkova et al, 2013] Jellemző fogyasztók a termelői piacokon Abelló et al, 2014;Berg -Preston, 2017;Grebitus et al, 2017 Fogyasztók és termelők közötti kölcsönhatásokat, motivációs különbségek Carson et al, 2016;Hunt, 2007;Leiper -Clarke-Sather, 2017 Termelői piacok működésében bekövetkező változások Bett et al, 2013;Blasi et al, 2015;Halldorsdottir -Nicholas, 2016 Helyi élelmiszerekkel szemben felmerülő attitűdök megítélése Asebo et al, 2007;Brown, 2003;Conner et al, 2010 Termelői piacok és a kereskedelmi egységek termékei közötti különbségek Bavorova et al, 2016 Fogyasztói tudatosság, fenntarthatóság és a termelői piacok környezetvédelmi előnyeinek fogyasztói észlelése Bozoglu et al, 2014;Szabó -Juhász, 2015;Dukeshire et al, 2015;Grebitus et al, 2017;Jadudova et al, 2018;Polimeni et al, 2018 Forrás: saját szerkesztés…”
Section: Példákunclassified
“…A társadalmi szempontok másfajta megközelítésében a termelő és fogyasztó közötti közvetlen kommunikáció és információcsere emelhető ki, amely a bizalmi kapcsolat megalapozásához elengedhetetlen. A környezeti szempontokkal kapcsolatos értékek egyre jelentősebb szerepet töltenek be világszerte, így a fenntarthatóság, a helyi gazdaságok támogatása, a származási hely és az ökológiai szempontok mind fontosak a fogyasztók számára [Baker et al, 2009;Bavorova et al, 2016;Blasi et al, 2015;Bozoglu et al, 2014;Carson et al, 2016;Conner et al, 2010;Dodds et al, 2014;Dukeshire et al, 2015;Fehrenbach -Wharton, 2012;Gumirakiza et al, 2014;Halldorsdottir -Nicholas, 2016;Leiper -Clarke-Sather, 2017]. A környezeti tényezőkkel kapcsolatos értékek azok, amelyek jellemzően a tudatos, képzett és felelősségteljes fogyasztók gondolkodásmódjában jelennek meg.…”
Section: A Termelői Piacok Fogyasztóinak Legfontosabb Motivációiunclassified
“…Milk is identified as a high-risk food product and the most important problem of the dairy sector in Turkey is low quality raw milk due to inadequate hygiene in dairy farms, transportation, storage and packaging facilities. High levels of contaminants in milk are detrimental to the health and well-being of Turkish consumers (Bozoglu et al , 2014) and the government is trying to improve food safety. One of these efforts ensured legislative alignment with the EU and international standards.…”
Section: Introductionmentioning
confidence: 99%
“…Ergönül (2013) evaluated consumer awareness and perception of food safety for several foods including dairy products and found that TV and radio programs were important information sources about food safety for consumers. Bozoglu et al (2014) assessed consumers’ purchase intention toward safety-labeled dairy products in Turkey and found that factors such as food safety concerns and satisfaction, residence, education and income have significant effects. While the above studies have contributed to an understanding of Turkish consumers’ concerns toward the safety of dairy products, their WTP for milk safety has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation